Effects of peptide-YY on the hypothalamic-pituitary-gonadal axis in healthy men - Izzi-Engbeaya,C; Jones,S; Crustna,Y; Machenahalli,PC; Papadopoulou,D; Modi,M; Panayi,C; Starikova,J; Eng,PC; Phylactou,M; Mills,E; Yang,L; et al. (Journal of Clinical Endocrinology and Metabolism, 2019)
ContextCentral and peripheral administration of peptide-YY (PYY) has potent anorectic effects, and PYY analogues are under development as anti-obesity treatments. Recent animal data suggest PYY may also influence the reproductive axis, however the effects of PYY on the human reproductive system are unknown.ObjectiveTo investigate the effects of PYY administration on the reproductive axis in healthy young men.DesignSingle-blind, randomised, placebo-controlled crossover study.SettingClinical Research Facility, Imperial College Healthcare NHS Trust.ParticipantsEighteen healthy eugonadal men (mean age 24.1±0.9years, mean BMI 22.2±0.4kg/m2).InterventionEight-hour intravenous infusion of 0.4pmol/kg/min PYY3-36 or rate-matched vehicle infusion.ResultsThe number of LH pulses (mean number of LH pulses/8hours: PYY 4.4±0.3 vs vehicle 4.4±0.4, p>0.99), LH area under the curve (AUC) (PYY 1503±79IU.min/L vs vehicle 1574±86IU.min/L, p=0.36), FSH AUC (PYY 1158±513IU.min/L vs vehicle 1199±476IU.min/L, p=0.49) and testosterone AUC (PYY 10485±684IU.min/L vs vehicle 11133±803IU.min/L, p=0.24) were similar during PYY and vehicle infusions.ConclusionsAcute intravenous infusion of 0.4pmol/kg/min PYY does not affect the reproductive axis in healthy men.